PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS TEKNOLOGI INFORMASI DENGAN MODEL TAM PADA HOTEL DI KABUPATEN GIANYAR - Nugraha, Amadeus Vincent Reziario; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
The aim of this study was to determine factors that affect acceptance of accounting information systems based on information technology in hotel Gianyar. Model TAM (Technology Acceptance Model) are used as variables or constructs in this study. TAM model consisted of two factors: perceived of usefulness, perceived ease of use, with the added convenience of perceived of enjoyment. This research was conducted in Gianyar. Sampling was done using judgmental (purposive). The data collection is done by distributing questionnaires to employees of the hotel accounting system of accounting information which has been determined by the users who use the system as a respondent. Data were analyzed using SEM analysis and GSCA (Generalized Structure Component Analysis) as a tool of analysis. The results showed that perceived of usefulness, perceived of ease of use and perceived of enjoyment has significant effect on attitudes. The attitude significantly influence the acceptance of information technology.
Keywords: Model TAM, Perceived of Usefulness, Perceived of Ease of Use, Perceived of Enjoyment, User Attitudes, Acceptance of Information Technology, GSCA